2002
DOI: 10.1523/jneurosci.22-21-09176.2002
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Characterization of GABA Transporters in Crayfish Neurosecretory Cells

Abstract: The effect of GABA on membrane potential and ionic currents of X-organ neurons isolated from the crayfish eyestalk was investigated. Under voltage-clamp conditions, GABA elicited an inward Na ϩ current followed by a sustained outward chloride current. Sodium current was partially blocked in a dose-dependent manner by antagonists of GABA plasma membrane transporters such as ␤-alanine, nipecotic acid, 1-[2([(diphenylmethylene)imino]oxy)ethyl]-1,2,5,6-tetrahydro-3-pyridinecarboxylic acid hydrochloride (NO 711), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
(47 reference statements)
1
7
1
2
Order By: Relevance
“…In the other 50% of the cells, Glu elicited a fully desensitizing current; similar results have been described previously (Duan and Cooke, 2000). By contrast, as previously reported in crayfish X-organ neurons (Garduño et al, 2002), GABA-evoked currents exhibited two components: an early transient inward current due to the electrogenic GABA uptake, followed by a sustained outward current generated through ligand-gated Cl -channels (Fig.·3A, middle trace). Finally, the HA-evoked current declined slowly during the continued application (Fig.·3A, right trace).…”
Section: Effects Of Ha On the X-organ Neuronssupporting
confidence: 88%
See 2 more Smart Citations
“…In the other 50% of the cells, Glu elicited a fully desensitizing current; similar results have been described previously (Duan and Cooke, 2000). By contrast, as previously reported in crayfish X-organ neurons (Garduño et al, 2002), GABA-evoked currents exhibited two components: an early transient inward current due to the electrogenic GABA uptake, followed by a sustained outward current generated through ligand-gated Cl -channels (Fig.·3A, middle trace). Finally, the HA-evoked current declined slowly during the continued application (Fig.·3A, right trace).…”
Section: Effects Of Ha On the X-organ Neuronssupporting
confidence: 88%
“…The HA-induced current was measured at the peak and these values were plotted against the log of the HA concentration, giving a concentration inducing a half-maximal response (EC 50 ) of 3.28±1·mol·l -1 and Hill number of 2.6±0.4 (Fig.·4B). The EC 50 value for HA differs considerably from those reported for Glu and GABA (Duan and Cooke, 2000;Garduño et al, 2002). Previous work has shown that the homomeric expression of the mRNAs encoding HA-gated Cl -channel subunits from the fruit fly Drosophila melanogaster produced HA receptors with EC 50 values of 166±12·mol·l -1 for DMHisCl-␣1 and 10.8±0.46 DM-HisCl-␣2 (Gisselmann et al, 2002), whereas those for HisCl-1 and HisCl-2 were 4.2±1.3 and 14±2.5, respectively (Zheng et al, 2002).…”
Section: Ha Dose-response Relationshipcontrasting
confidence: 66%
See 1 more Smart Citation
“…Nipecotic acid, a cyclic analog of GABA, and ␤-alanine are competitive inhibitors of GABA transporters (14) and likely bind to the same site as the GABA (or betaine) substrate (46). These results suggest that the conformational stability of the transport site, or the fidelity of the transport function, is not required for the signals that regulate insertion of protein into the plasma membrane.…”
Section: Discussionmentioning
confidence: 97%
“…C3H/10T 1 ⁄2 mouse embryo fibroblasts (43) (CCL-226; American Type Culture Collection) were cultured in DMEM containing 10% heat-inactivated fetal bovine serum, 25 mM NaHCO3, 5 mM HEPES, penicillin (50 U/ml), and streptomycin (50 g/ml). The cells were maintained as subconfluent monolayers and were used between passages [5][6][7][8][9][10][11][12][13][14][15]. Both cell lines were maintained at 37°C in an atmosphere of 5% CO2 in air.…”
Section: Methodsmentioning
confidence: 99%